Sosialisasi Teknik Self-Token Economy untuk Meningkatkan Motivasi Akademik Anak Panti Asuhan Muhammadiyah Nuruddin Kota Banjarmasin - Yulizar Abidarda; Sanjaya Sanjaya; Rudi Haryadi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The Socialization Program of Self-Token Economy Techniques was carried out at the Muhammadiyah Nuruddin Orphanage with the main goal of increasing the academic motivation of orphanage children through a token-based reward system approach. Children in orphanages often face challenges such as low motivation to learn, lack of incentive systems, lack of confidence, and an unconducive learning environment. To answer these problems, this program prioritizes the Self-Token Economy technique as an educational and applicative intervention strategy. The implementation method consists of the preparation stage, the implementation of socialization, and impact evaluation. The target of the activity was 15 orphanage children who were actively involved in the entire series of programs. This activity also involves strategic partners who play a role in providing facilities, technical assistance, and program sustainability planning. The results showed an increase in participants' academic motivation, characterized by increased participation in learning activities, understanding of the award system, and the emergence of independent learning initiatives. In addition, this program produces outputs in the form of scientific publications as a form of dissemination of knowledge and good practices in developing the academic motivation of orphanage children. In conclusion, the Self-Token Economy technique has proven to be effective as a social intervention approach that can be applied in the orphanage environment to support the achievement of children's education more optimally.